Laser Ablation of Abnormal Neurological Tissue Using Robotic NeuroBlate System (LAANTERN): 12-Month Outcomes and Quality of Life After Brain Tumor Ablation. Issue 3 (21st April 2020) - Kim, Albert H; Tatter, Steven; Rao, Ganesh; Prabhu, Sujit; Chen, Clark; Fecci, Peter; Chiang, Veronica; Smith, Kris; Williams, Brian J; Mohammadi, Alireza M; Judy, Kevin; Sloan, Andrew; et al.
Abstract: BACKGROUND: Laser Ablation of Abnormal Neurological Tissue using Robotic NeuroBlate System (LAANTERN) is an ongoing multicenter prospective NeuroBlate (Monteris Medical) LITT (laser interstitial thermal therapy) registry collecting real-world outcomes and quality-of-life (QoL) data. OBJECTIVE: To compare 12-mo outcomes from all subjects undergoing LITT for intracranial tumors/neoplasms. METHODS: Demographics, intraprocedural data, adverse events, QoL, hospitalizations, health economics, and survival data are collected; standard data management and monitoring occur. RESULTS: A total of 14 centers enrolled 223 subjects; the median follow-up was 223 d. There were 119 (53.4%) females and 104 (46.6%) males. The median age was 54.3 yr (range 3-86) and 72.6% had at least 1 baseline comorbidity. The median baseline Karnofsky Performance Score (KPS) was 90. Of the ablated tumors, 131 were primary and 92 were metastatic. Most patients with primary tumors had high-grade gliomas (80.9%). Patients with metastatic cancer had recurrence (50.6%) or radiation necrosis (40%). The median postprocedure hospital stay was 33.4 h (12.7-733.4). The 1-yr estimated survival rate was 73%, and this was not impacted by disease etiology. Patient-reported QoL as assessed by the Functional Assessment of Cancer Therapy-Brain was stabilized postprocedure. KPS declined by an average of 5.7 to 10.5 points postprocedure; however, 50.5% had stabilized/improved KPS at 6 mo. There were no significant differences in KPS or QoL between patients with metastatic vs primary tumors. CONCLUSION: Results from the ongoing LAANTERN registry demonstrate that LITT stabilizes and improves QoL from baseline levels in a malignant brain tumor patient population with high rates of comorbidities. Overall survival was better than anticipated for a real-world registry and comparative to published literature. Graphical Abstract: